COVID-19 Impacts on Stock Return outlooks of Stock Exchange listed Aviation Transport Companies in India - Dr.R.Amuthan (International Journal of Advanced Science and Technology, 2020)
Air Travel Industry is one of Industries in India which meet with unprecedented financial losses ever since the introduction of Goods and Service Tax, additional exercise duty on Air Turbine fuel etc. Now this COVID-19 Pandemic is certainly a final nail in their coffins. Without leaving anything for a chance, all the five listed Airlines Companies have been meeting with unprecedented losses on account of dent in their demands to Asia from the rest of the world. Even before the declaration of pandemic by World Health Organization, all most all flights to China were cancelled and their locations in Asia as well on account of Coronavirus related fears among air travel passengers. Less than a week, this industry happened to see a huge virus spread to Europe followed by The America and Africa. This incident led this industry to receive catastrophe losses and all their price reduction strategies and Discounts etc., became ill-conceived. Adding fuel to flames is that they do not hear any kind of bail out packages so far from the Government as good as U.S.Airlines.U.S. Administration had passed a stimulus bill which includes $58 billion in aid for Airlines.-29 billion in Pay roll grants for workers and $29 billion in loans for the airlines.As per the estimate of International Air Transport (IATA), there will be $314 billion losses due to this COVID-19 outbreak.